Nilai-Nilai Pendidikan Islam dalam Ekstrakurikuler Berkuda dan Pengaruhnya terhadap Peningkatan Karakter Baku di SMA Daarut Tauhiid Bandung - Yayan Rusmana (Program Pascasarjana Universitas Ibrahimy, 2019)
One of environment that can affect individual character is school or education environment. The educational environment can shape the character of each individual according to what is taught in their activities. School is a place that is used as a place, including also taught norms, values, boundaries in doing, and acting so that they are expected to be personal by the nation and state. Likewise horse riding extracurricular activities at Daarut Tauhiid High School Bandung. This study aims to: 1) find out the values ​​of Islamic education in equestrian extracurricular activities, 2) know the implementation, 3) know the inhibiting and supporting factors, 4) know the effect on BAKU character education. The method used is a case study with qualitative research. The results of the research and discussion, that of equestrian extracurricular there are values ​​of Islamic education such as leadership, taaruf values​​. In addition, from the results the spread of questionnaires to students’ perceptions of the influence of BAKU character education were fairly good. This is seen from the results of a percentage of 53% the good category of the results of the questionnaire of 55 people.